The Cytotoxicity of Agaro-Oligosaccharides and Neoagaro-Oligosaccharides on Macrophage Cells - Pratitis, Visi Endah; Puspitasari, Pinki Anggrahini; Hanbal, Mayland Muhammad; Tsabitah, Khansa; Juliadmi, Dian; Saksono, Budi; Wijayanti, Nastiti (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2024)
Agarose is a polysaccharide from red algae. Enzymatic hydrolysis of agarose can produce Agaro-Oligosaccharidess (AOS) and Neoagaro-Oligosaccharidess (NAOS). Different times of enzymatic hydrolysis can produce different types of AOS and NAOS based on their degree of polymerization (DPs). This study aims to examine the cytotoxicity of AOS and NAOS with different hydrolysis times on the macrophage cell line RAW 264.7. The parameters used were the percentage of cell viability and IC50 value. The cytotoxicity test using MTT assay and One-way ANOVA were used as statistical tests. The results showed that AOS-0 at a concentration below 125 µg/mL was not toxic and showed moderate toxicity up to a high concentration of 1000 µg/mL, while AOS hydrolyzed for 24 h (AOS-24) was not toxic to RAW 264.7 cells at all concentrations tested. The different results were shown in all NAOS samples, which were highly toxic to RAW 264.7 cells in the 125 to 1000 µg/mL, indicating that it was concentration dependent. The results showed that different hydrolysis times caused differences in the structure of AOS and NAOS compounds and influenced the toxicity level. Research development for further studies on antioxidants and anti-inflammatory needs more attention to the sample type and hydrolysis time.